Perancangan Layout Penempatan Material pada Gudang PT. XYZ untuk Implementasi Sistem FIFO - Jezreel Willy Adichnadra; Herry Christian Palit (Jurnal Titra, 2022)
The problem that exists in the warehouse at PT. XYZ is that there is no material placement layout in the warehouse that supports the FIFO system. The proposal given is to make a layout of material placement in the warehouse by calculating the number of pallets used for each existing material and making a storage and retrieval mechanism that supports the FIFO system will run better. The proposed results can create a more friendly environment for the FIFO system. The ABC method is the main method used to determine the priority of material mapping on the shelves in the warehouse. Then by finding the right order of priority, the calculation to determine the number of pallets used for each material will be easier to find and do. The calculation of the use of pallets that have been obtained will be a reference for the exact location of the material on the shelves in the warehouse, so that the placement of materials in the warehouse will be arranged which creates an environment that makes it easy to find each material to be found and the FIFO system will be easier to run.